Biofilm-Grown Burkholderia cepacia Complex Cells Survive Antibiotic Treatment by Avoiding Production of Reactive Oxygen Species - Van Acker, Heleen; Sass, Andrea; Bazzini, Silvia; De Roy, Karen; Udine, Claudia; Messiaen, Thomas; Riccardi, Giovanna; Boon, Nico; Nelis, Hans J.; Mahenthiralingam, Eshwar; Coenye, Tom (PLOS ONE, 2013)
The presence of persister cells has been proposed as a factor in biofilm resilience. In the present study we investigated whether persister cells are present in Burkholderia cepacia complex (Bcc) biofilms, what the molecular basis of antimicrobial tolerance in Bcc persisters is, and how persisters can be eradicated from Bcc biofilms. After treatment of Bcc biofilms with high concentrations of various antibiotics often a small subpopulation survived. To investigate the molecular mechanism of tolerance in this subpopulation, Burkholderia cenocepacia biofilms were treated with 1024 µg/ml of tobramycin. Using ROS-specific staining and flow cytometry, we showed that tobramycin increased ROS production in treated sessile cells. However, approximately 0.1% of all sessile cells survived the treatment. A transcriptome analysis showed that several genes from the tricarboxylic acid cycle and genes involved in the electron transport chain were downregulated. In contrast, genes from the glyoxylate shunt were upregulated. These data indicate that protection against ROS is important for the survival of persisters. To confirm this, we determined the number of persisters in biofilms formed by catalase mutants. The persister fraction in ΔkatA and ΔkatB biofilms was significantly reduced, confirming the role of ROS detoxification in persister survival. Pretreatment of B. cenocepacia biofilms with itaconate, an inhibitor of isocitrate lyase (ICL), the first enzyme in the glyoxylate shunt, reduced the persister fraction approx. 10-fold when the biofilms were subsequently treated with tobramycin. In conclusion, most Bcc biofilms contain a significant fraction of persisters that survive treatment with high doses of tobramycin. The surviving persister cells downregulate the TCA cycle to avoid production of ROS and at the same time activate an alternative pathway, the glyoxylate shunt. This pathway may present a novel target for combination therapy.